The impact of Venture Capital on the Sales and Profitability performance of Portfolio Firms in the Indian Market - Mathur, Vidur (2015)
This study uses a matched dataset of 59 public and private Venture-backed firms operating in the Indian economy, along with their equivalent control group of non-Venture-backed firms, with observations recorded between 2001 and 2010. It first conducts an analysis to determine the factors which inform the likelihood of receiving Venture Capital funding in India (Using a Probit Model). Further, it systematically investigates the impact of Venture Capital funding on the performance of Indian portfolio firms, given by changes in their sales and profitability performance in the post funding period (Using OLS). After accounting for Sample Selection Bias and running a Fixed Effects Panel Data Model with a Heteroscedasticity and Serial Correlation correction, the study finds weak but significant evidence that Venture Capital funding positively impacts the sales of portfolio firms. Further, it finds that this positive impact is not immediate. The study also finds strong evidence that Venture Capital has an immediate and negative impact on the profitability of portfolio firms in the post funding period. The findings for sales are consistent with the bulk of existing literature. The findings for profitability contrast with existing theoretical evidence regarding the impact of Venture Capital funding on firm performance, however, these findings are also consistent with an existing strain of literature. Further, to the best of the author’s knowledge, this study represents the first empirical analysis of the firm-level impacts of Venture Capital in India. The study thus makes an important contribution to the debate regarding the impact of Venture Capital funding and is valuable from the perspective of the investor, entrepreneur and policy maker.